Proteomic analysis of the cardiac myocyte secretome reveals extracellular protective functions for the ER stress response - Blackwood, Erik A.; Thuerauf, Donna J.; Stastna, Miroslava; Stephens, Haley; Sand, Zoe; Pentoney, Amber; Azizi, Khalid; Jakobi, Tobias; Van Eyk, Jennifer E.; Katus, Hugo; Glembotski, Christopher C.; Doroudgar, Shirin (Journal of molecular and cellular cardiology, 2020)
The effects of ER stress on protein secretion by cardiac myocytes are not well understood. In this study, the ER stressor thapsigargin (TG), which depletes ER calcium, induced death of cultured neonatal rat ventricular myocytes (NRVMs) in high media volume but fostered protection in low media volume. In contrast, another ER stressor, tunicamycin (TM), a protein glycosylation inhibitor, induced NRVM death in all media volumes, suggesting that protective proteins were secreted in response to TG but not TM. Proteomic analyses of TG- and TM-conditioned media showed that the secretion of most proteins was inhibited by TG and TM; however, secretion of several ER-resident proteins, including GRP78 was increased by TG but not TM. Simulated ischemia, which decreases ER/SR calcium also increased secretion of these proteins. Mechanistically, secreted GRP78 was shown to enhance survival of NRVMs by collaborating with a cell-surface protein, CRIPTO, to activate protective AKT signaling and to inhibit death-promoting SMAD2 signaling. Thus, proteins secreted during ER stress mediated by ER calcium depletion can enhance cardiac myocyte viability.